Sediment Sources Analysis Using CSSI Method in Pasir Buncir Micro-watershed, Bogor, Indonesia - B. Aliyanta; P. Sidauruk (PPIKSN-BATAN, 2019)
There is an increasing need for reliable information concerning the source of the suspended sediment transported by rivers. Such information is required both to design effective sediment and non-point pollution control strategies and to provide an improved understanding of erosion and suspended sediment transport within a watershed. In some situations, there are many developing methods of fingerprinting to determine the contribution of sediment sources via the streambed sediment. In this study, compound-specific stable isotope (CSSI) fingerprint has been used to determine sediment source contribution in Pasir Buncir micro-watershed, Bogor, West Java. CSSI method is a newly developed technique in sediment sources contribution determination. This new technique is considered to be a very accurate technique for identifying the sediment sources contribution, especially in a watershed that has relatively similar soil types. This technique has been applied to studying the sediment source contribution study in a watershed with three different land uses with mostly clay loam soil type. One sample from each of three different land uses was collected vertically from the 0-2 cm depth range. Streambed sediment from the nearest outlet from the micro-watershed was also collected. Soil and streambed sediment samples were analyzed for d13C of bulk organic carbon and CSSI contents. The d13C of bulk organic carbon and CSSI contents analysis showed that all the three different land uses (one-season crop, intercropping, and pine forest) contributed to streambed sediment; approximately 79.2 % was from cultivated land of one-season crop, 15.2 %from intercropping land, and 5.6 % from pine forest.